Pengaruh Media Loose Part Terhadap Perkembangan Motorik Halus Pada Anak Kelompok B Di PAUD Taam An Nuur Palembang Tahun 2023 - Febriyanti, Febriyanti; Novianti, Rahmah; Ahmad, Syarwani (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to analyze how fine motoric skills can be developed in children using loose part media. The research method used in this study is an experimental technique, namely a strategy to determine whether a variable has an influence on other variables or there is a causal relationship between two variables. Collecting data in this research uses 3 techniques, namely observation, testing, and documentation. Data analysis used regularity test and homogeneity test. Based on research that has been conducted at PAUD Taam An Nuur to develop children's fine motoric skills by using loose part media in learning process activities. Because through this research it can be proven that there is an effect of using loose part media on fine motoric skills in group B children at PAUD Taam An Nuur. This can be seen from the initial state of the pretest which obtained an average value of 54.539 after being given the treatment the final posttest results showed an average value of 88.778.Thus, it can be seen that the posttest average value is greater than the pretest average value of 88.778 ≥ 54.539. Furthermore, the results of the calculation of the t-test hypothesis testing obtained Sig. (1-tailed) = 0.000 < α 0.05, means that Ha is accepted and H0 is rejected. In this way it can be concluded that this study has the effect of loose part media on fine motor development in group B children at PAUD Taam An Nuur. Keywords: Fine Motor Development, Loose Part Media.